PERAN PEMERINTAH KABUPATEN MAGELANG DALAM PENDAFTARAN INDIKASI GEOGRAFIS - Karlina Lubis, Ria; Cahya Nugrahenti, Meydora; Pajrin, Rani Pajrin (Mendapo: Journal of Administrative Law, 2022)
The purpose of this research is to know the roles and responsibilities of the Regional Government of Magelang Regency in developing, empowering and registering Geographical Indications and knowing the various obstacles faced by the Magelang Regency Government in efforts to develop, empower and register Geographical Indications. Geographical indication rights are important for producers/Geographical Indication Protection Society (MPIG) and consumers in recognizing the products produced. Signs of Geographical Indications have both legal and economic implications for MPIG. Methods This research was conducted in the field or field research with the type of empirical legal research or social legal research. The data used are primary data and secondary data and secondary data related to the research conducted. The secondary data consists of primary legal materials, secondary legal materials and tertiary legal materials. The roles and responsibilities of the local government of Magelang Regency include the development, empowerment, registration and supervision of geographical indications. While the obstacles faced by the Regional Government of Magelang Regency are the absence of a Regional Regulation so that the grand design of Geographical Indications in Magelang Regency does not yet exist, on the other hand the understanding and knowledge of both the Regional Government and the community do not fully understand the process of registering geographical indications and post registration of geographical indications.